Ride Test on Vehicles Travelling Over Speed Bumps: Simulation with CarSim Software - Adetia Lenahatu; Mohamad Yamin (Universitas Mercu Buana, 2024)
This study explores the effects of different speed bump geometries—flat-topped, sinusoidal, and parabolic—on vehicle dynamics and ride comfort using CarSim simulations. The analysis focuses on key parameters such as vertical forces on the suspension, vertical acceleration, and the wheel surface adhesion index. The results show that flat-topped bumps generate the highest vertical forces, reaching peaks of up to 6,000 N on the front suspension, leading to increased discomfort. Sinusoidal bumps, in contrast, generate smoother transitions, with vertical forces peaking at approximately 3,500 N, improving ride comfort. At vehicle speeds of 30 km/h, the vertical forces on the suspension increase significantly, with flat-topped bumps reducing the wheel surface adhesion index to as low as 0.6, indicating a higher risk of wheel slip and compromised vehicle stability. In contrast, sinusoidal bumps maintain a more favorable adhesion index of 0.85 at similar speeds. These reductions in adhesion elevate the risk of loss of control, especially at higher speeds. The findings suggest that adaptive suspension systems, capable of adjusting damping and stiffness based on the bump geometry and vehicle speed, would enhance ride quality and stability. Additionally, smoother bump designs, such as sinusoidal profiles, are recommended to reduce the impact on vehicle dynamics, particularly in urban environments. These insights contribute to improving both vehicle design and road safety, ensuring safer and more comfortable driving experiences.